PENILAIAN TINGKAT KEPUASAN WISATAWAN TERHADAP PENERAPAN PROKES DAN PERKEMBANGAN FASILITAS WISATA PERKEBUNAN TEH NGLINGGO - Novi Irawati; Meiana Maulida Hikmawati; Ervita Lusiana Utari (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
The Covid-19 pandemic has had a very severe negative impact on tourism activities and the economy of the community in the Nglinggo Tea Plantation Tourism Area. The development of tourist attractions, development of MSMEs, improvement of access and application of health protocols for visiting tourists continues. However, it is not enough to increase the value of visits. This is what makes the reason in the study the importance of assessing the level of satisfaction of tourists visiting the Nglinggo Tea Plantation Area during this pandemic as the basis for planning strategic programs that can boost tourist visits back to the Nglinggo Tea Plantation Area. This quantitative research uses the Importance Performance Analysis (IPA) technique with tourists visiting the Nglinggo Tea Plantation Tourism area during the pandemic as respondents. Based on the results of research that has been carried out, tourists express their satisfaction with all the efforts made by the manager, the community and the government, such as the availability of supporting facilities for health protocols, good nature and culture conservation, empowered local communities through MSMEs, and integrated collaboration with shareholders. However, there are several variables that are declared to have no effect and are not a priority for certain tourists, so there needs to be a re-examination in the use of more targeted development.Keywords: Product Quality Perception, Customer Satisfaction, Importance Performance Analysis, Covid-19